Implementation of a non intrusive software component to monitor web applications in a public entity - Santos López, Félix Melchor (2013)
Importance of measuring the response time of web applications is transcendental for decisionmaking and/or corrections on the part of public officials involved in the departments of information systems and technologies. This research provides the conceptual framework for the development of a component J2EE (Java 2 Enterprise Edition) non-intrusive through Web Servlet filters and Interceptors of Spring Framework. It also uses the communication protocol TCP/IP for sending frames in JSON format (JavaScript Object Notation) and its subsequent reception for a stand-alone component for the record in a database. Finally, a hypothesis test between Log4j and Socket Simple technologies is performed, achieving an average record time of the plots approximately 0.05 seconds, and report that there are no statistical evidences to affirm that one is better and faster than the other.